Al-Qur’an dan Karakteristik Masyarakat Muslim - Muhammad Hatta Diponegoro (Jurnal Keislaman, 2020)
Abstract: Muslim society is an open society that upholds universal values ​​of humanity and life, regardless of ethnic origin and religious differences. The Muslim community is a group of people who work together and live together based on the principles of the Qur'an and Hadith in their lives. Society in the view of Islam is a means to carry out Islamic teachings concerning life together. For this reason, society must become the basis for the framework of worldly life for the unity and cooperation of the people towards a human growth that embodies equality and justice. It is not called an Islamic society if it is always filled with feelings of revenge, which arise as a result of social injustice and mistreatment of some people towards others. This form of interaction is not recognized in Islam.The characteristics of a Muslim society are a society that has positive qualities and upholds the virtues taught by Islam. Each member of the community plays their respective roles to build a harmonious society by reflecting harmony. Peace and harmony are the main characteristics of an Islamic society.